Mohamed Enver Surty’s In Pursuit of Dignity - Hussain Savant (The Thinker)
In Pursuit of Dignity is the unusual autobiography of our erstwhile Deputy Minister of Basic Education, Mohamed Enver Surty. The author served in government for twenty five years with distinction, and can be justly proud of a distinguished career both as a lawyer and as a government minister.